A novel titanium alloy manufactured by selective laser melting: Microstructure, high temperature oxidation resistance. (5th January 2016) - Zhou, Y.; Wen, S.F.; Song, B.; Zhou, X.; Teng, Q.; Wei, Q.S.; Shi, Y.S.
Abstract: A novel titanium alloy (Ti–5.5Al–3.4Sn–3.0Zr–0.7Mo–0.3Si–0.4Nb–0.35Ta) with a relative density of 99.34% was produced by selective laser melting (SLM) under the condition of 140 W laser power and 400 mm/s scanning speed. The microstructure, high temperature oxidation resistance and micro-hardness were studied. The results showed that the acicular martensitic α′ phase was about 0.5 μm in width due to the high cooling rate during the SLM process. The comparative measurements showed that the as-SLMed sample had higher oxidation resistance and micro-hardness than those of the as-casted one. And the oxidation mechanism was proposed. Graphical abstract: Highlights: A novel Ti alloy with a relative density of 99.34% was formed by SLM. The acicular martensitic α′ phase was observed in the SLMed sample. The SLMed sample showed higher oxidation resistant than that of a casted sample one. The Vickers micro-hardness reached 612 Hv for SLMed sample.